The impact of financial accounting disclosures on investors' reactions towards bad news: The moderating role of investors' sentiments - Shatha Mustafa Hussain; Amer Alaya; Thana A. Azizi (Cogent Economics & Finance, 2023)
This paper examines the influence of financial accounting disclosures (FAD) on the investors' reactions towards bad news (IRBN), and analytically assesses the moderation effect of the individual investor's sentiments particularly" Subjective norms" on that relationship in project-based organizations (PBOs) listed in the UAE financial markets from a financial, and psychological perspective. Structural equation modelling (SEM) was used to analyse 310 completed questionnaires using Statistical Package for Social Sciences (SPSS) and Analysis of Moment Structures (AMOS) by multiple regression, path, and moderation analysis. Findings show that four dimensions of the studied FAD have a direct positive impact on the IRBN except for the external auditing and audit service (EAUS). Results also revealed that the subjective norms have a moderating impact on the relationship between FAD and the IRBN. Academically, this research contributes to both the reasoned action theory and the agency theory and satisfies an important gap in FAD literature. Practically, organizations, policymakers, and officials can use the findings of reliable and valid measurements of FAD, IRBN, and investors' sentiment items to control and develop purposes, as IRBN can be controlled by healthy communication tools via different disclosure channels and healthy disclosure content. Investor Relations (IR) managers can realize if the desired disclosure is well comprehended in investors' awareness, trust, intention, and perceptual reaction. It is one of the first empirical studies to establish a model illustrating the relationships between FAD, Subjective norms, and IRBN. The proposed model comprises processes and practices that could be used to enhance the decision-making process of investors and control their reactions that impact PBOs in the United Arab Emirates (UAE).
Keywords: 330; Financial Accounting Disclosures (FAD); Investors' Reactions Towards Bad News (IRBN); Investors' Sentiments (IS); Project-Based Organizations (PBOs); Subjective Norms (SN)